Adsorbing material as well as preparation method and application thereof
By performing acid treatment and hydrothermal reaction on the negative electrode material of waste lithium-ion batteries, combined with the participation of manganese source, an adsorption material with high pore capacity and specific surface area was prepared, which solved the problem of poor performance of the negative electrode material and achieved the effect of heavy metal pollutants. Highly efficient adsorption.
Patent Information
- Application Number
- CN202411647555.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of adsorption materials, and in particular relates to an adsorption material and a preparation method and use thereof. Background Art
[0002] With the booming electric vehicle market, a huge number of waste power batteries have been generated. Considering the pollution of hazardous waste to the environment and the scarcity of resources, the recycling of waste lithium-ion batteries has important economic value and practical significance. In recent years, the recycling of positive electrode materials (such as high-value metals such as cobalt, nickel and lithium) has made considerable progress, but the regeneration of negative electrode materials with lower added value (mainly graphite) has rarely been mentioned. However, the negative electrode materials in waste batteries currently have a series of poor properties such as pore volume, specific surface area and purity, which cannot be effectively utilized. Summary of the invention
[0003] The purpose of the present invention is to provide an adsorption material, a preparation method and use thereof. The adsorption material prepared by the method provided by the present invention using the negative electrode material in waste batteries has excellent pore volume and specific surface area and high purity. The adsorption material provided by the present invention has significant advantages in adsorbing heavy metal pollutants, with a low heavy metal residual rate and little material loss after the reaction.
[0004] In order to achieve the above object, the first aspect of the present invention provides a method for preparing an adsorbent material, wherein the method comprises: S0, discharging and disassembling the waste battery to obtain the negative electrode sheet; S1, subjecting the negative electrode sheet to an acid treatment, and then performing solid-liquid separation to obtain a negative electrode material; S2, mixing the negative electrode material with a manganese source, performing a first hydrothermal reaction, and obtaining a mixed product; S3, subjecting the mixed product to a second hydrothermal reaction with an alkaline solution and collecting a solid phase product.
[0005] Optionally, the waste battery is a battery whose negative electrode contains carbon material; The discharging comprises: immersing the waste battery in a sodium chloride or sodium sulfate aqueous solution with a mass concentration of more than 0.2 mol / L for more than 2 hours.
[0006] Optionally, the concentration of the acid solution in the acid treatment is above 2 mol / L; the acid solution comprises an oxygen-containing acid, preferably one or more of nitric acid, sulfuric acid and perchloric acid; The acid treatment temperature is above 50°C, preferably 60-90°C; the time is 2-24h, preferably 3-12h; The ratio of the volume of the acid solution to the mass of the negative electrode is 4 or more.
[0007] Optionally, the mass ratio of the negative electrode material to the manganese source is (20-40):1; The manganese source includes one or more of potassium permanganate, manganese dioxide and manganese nitrate; The concentration of the manganese source is 0.5-8 mol / L.
[0008] Optionally, in step S2, the conditions of the first hydrothermal reaction include: a temperature of 90° C. or higher, preferably 90-110° C.; and a time of 30 min or higher, preferably 40-120 min.
[0009] Optionally, in step S3, the conditions of the second hydrothermal reaction include: a temperature of 60° C. or higher, preferably 90-110° C.; a time of 60 min or higher, preferably 60-240 min; The alkaline solution is selected from sodium hydroxide solution and / or potassium hydroxide solution; the concentration of the alkaline solution is above 5%.
[0010] Optionally, the method further comprises: in step S3, after the second hydrothermal reaction, recovering the solid phase product, washing and drying it to obtain an adsorption material; The drying temperature is above 80° C. and the drying time is above 8 hours.
[0011] The second aspect of the present invention provides an adsorption material prepared by the method described in the first aspect of the present invention.
[0012] Optionally, the adsorbent material comprises C and manganese oxide; The specific surface area of the adsorption material is 260 m 2 / g or more, preferably 280m 2 / g or more; pore volume is 0.7cm 3 / g or more, preferably 0.9cm 3 / g or above.
[0013] The third aspect of the present invention provides use of the adsorption material described in the second aspect of the present invention in adsorbing heavy metal pollutants.
[0014] Through the above technical scheme, the present invention performs an acid treatment on the negative electrode in the waste battery, and then mixes it with a manganese source to perform a first hydrothermal reaction to obtain a mixed product, and then the mixed product is subjected to a second hydrothermal reaction with an alkaline solution to prepare a catalytic material. The method provided by the present invention causes the negative electrode material in the waste battery to undergo a hydrothermal reaction with a manganese source to produce more pores and active sites, and then the mixed product is subjected to a secondary hydrothermal reaction with an alkaline solution, which can further increase the pore volume of the prepared adsorption material, so that the material has a higher specific surface area, and further increase the adsorption sites of the material, so that the material has more excellent adsorption performance. The adsorption material provided by the present invention has significant advantages in the adsorption of heavy metal pollutants, with a low heavy metal residual rate and less material loss after the reaction.
[0015] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0016] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0017] A first aspect of the present disclosure provides a method for preparing an adsorbent material, wherein the method comprises: S0, discharging and disassembling the waste battery to obtain the negative electrode sheet; S1, subjecting the negative electrode sheet to an acid treatment, and then performing solid-liquid separation to obtain a negative electrode material; S2, mixing the negative electrode material with a manganese source, performing a first hydrothermal reaction, and obtaining a mixed product; S3, subjecting the mixed product to a second hydrothermal reaction with an alkaline solution and collecting a solid phase product.
[0018] The method provided by the present invention allows the negative electrode material in the waste battery to undergo a hydrothermal reaction with a manganese source to generate more pores and active sites, and then allows the mixed product to undergo a secondary hydrothermal reaction with an alkaline solution, which can further increase the pore volume of the prepared adsorption material, allow the material to have a higher specific surface area, and further increase the adsorption sites of the material, thereby allowing the material to have more excellent adsorption performance. The adsorption material provided by the present invention has significant advantages in being used for adsorbing heavy metal pollutants, with a low heavy metal residual rate and little material loss after the reaction.
[0019] In a specific embodiment, the waste battery is a battery whose negative electrode contains carbon material.
[0020] In a specific embodiment, the discharging includes: immersing the waste battery in a sodium chloride or sodium sulfate aqueous solution with a concentration of 0.2 mol / L or more for more than 2 hours.
[0021] In a specific embodiment, the concentration of the acid solution in the acid treatment is 2 mol / L or more, preferably 2-6 mol / L.
[0022] In a specific embodiment, the acid solution includes an oxygen-containing acid, preferably one or more of nitric acid, sulfuric acid and perchloric acid.
[0023] In a specific embodiment, the acid treatment is carried out at a temperature of 50° C. or above, preferably 60 to 90° C., and for a time of 2 to 24 hours, preferably 3 to 12 hours.
[0024] In a specific embodiment, the ratio of the volume of the acid solution to the mass of the negative electrode is greater than 4, preferably 6 to 12. In the above embodiment, controlling the mass ratio of the acid solution to the negative electrode within the preferred range of the present application can further improve the comprehensive performance of the prepared material.
[0025] In a specific embodiment, the mass ratio of the negative electrode material to the manganese source is (20-40): 1, preferably (25-35): 1. In the above embodiment, controlling the mass ratio of the negative electrode material to the manganese source within the preferred range of the present application can further improve the adsorption performance of the prepared material.
[0026] In a specific embodiment, the manganese source includes one or more of potassium permanganate, manganese dioxide and manganese nitrate, preferably potassium permanganate.
[0027] In a specific embodiment, the concentration of the manganese source is 0.5-8 mol / L or more, preferably 2-6 mol / L.
[0028] In a specific embodiment, in step S2, the conditions of the first hydrothermal reaction include: a temperature of 90° C. or higher, preferably 90-110° C.; and a time of 30 min or higher, preferably 40-120 min.
[0029] In a specific embodiment, in step S3, the conditions of the second hydrothermal reaction include: a temperature of 60° C. or higher, preferably 90-110° C.; and a time of 60 min or higher, preferably 60-120 min.
[0030] In a specific embodiment, the alkaline solution is selected from sodium hydroxide solution and / or potassium hydroxide solution, preferably sodium hydroxide solution; the concentration of the alkaline solution is above 5%, preferably 8-12%.
[0031] In a specific embodiment, the method further comprises: in step S3, after the second hydrothermal reaction, recovering the solid phase product, washing and drying it to obtain an adsorption material.
[0032] In a specific embodiment, the drying temperature is above 80° C., preferably 70-90° C.; the drying time is above 8 hours, preferably 18-36 hours.
[0033] A second aspect of the present disclosure provides an adsorption material prepared by the method described in the first aspect of the present disclosure.
[0034] In one embodiment, the adsorbent material comprises C and manganese oxide.
[0035] In a specific embodiment, the specific surface area of the adsorbent material is 260m 2 / g or more, preferably 280m 2 / g or more; pore volume is 0.7cm 3 / g or more, preferably 0.9cm 3 / g or above.
[0036] The third aspect of the present disclosure provides use of the adsorption material described in the second aspect of the present disclosure in adsorbing heavy metal pollutants.
[0037] The adsorption material provided by the present disclosure has excellent pore volume and specific surface area, and high purity. The adsorption material provided by the present invention has significant advantages in being used for adsorbing heavy metal pollutants, with a low heavy metal residual rate and little material loss after the reaction.
[0038] The present invention is further described below by way of examples, but the present invention is not limited thereby. The raw materials used in the examples and comparative examples can be obtained through commercial channels.
[0039] Example 1 a. Immerse the conventional commercially available waste lithium batteries in a sodium chloride solution with a mass concentration of 2 mol / L for 4 hours for discharge, and then disassemble them to obtain the negative electrode sheet.
[0040] b. The negative electrode sheet in step a is subjected to acid treatment, and then solid-liquid separation is performed to obtain a negative electrode material; wherein the concentration of the acid solution in the acid treatment is 4 mol / L, the acid solution is a nitric acid solution, and the ratio of the volume of the acid solution to the mass of the negative electrode is 10:1; the temperature of the acid treatment is 90° C., and the time of the acid treatment is 4 hours.
[0041] c. Mix the negative electrode material in step b with a manganese source, perform a first hydrothermal reaction, and obtain a mixed product; wherein the manganese source is potassium permanganate, the concentration of the manganese source is 4 mol / L, and the mass ratio of the negative electrode material to the manganese source is 30:1; the temperature of the first hydrothermal reaction is 100° C., and the reaction time is 40 min.
[0042] d. subjecting the mixed product to a second hydrothermal reaction with an alkaline solution, taking out the solid phase product, washing it, and then drying it to obtain an adsorbent material; wherein the alkaline solution is a sodium hydroxide solution, the concentration of the alkaline solution is 10%, the temperature of the second hydrothermal reaction is 100° C., the reaction time is 60 min, the drying temperature is 80° C., and the drying time is 24 h.
[0043] Example 2 a. Immerse the conventional commercially available waste lithium batteries in a sodium chloride solution with a mass concentration of 4 mol / L, soak for 4 hours for discharge, and then disassemble to obtain the negative electrode.
[0044] b. The negative electrode in step a is subjected to acid treatment, and then solid-liquid separation is performed to obtain a negative electrode material; wherein the concentration of the acid solution in the acid treatment is 6 mol / L, the acid solution is a sulfuric acid solution, and the ratio of the volume of the acid solution to the mass of the negative electrode is 10:1; the temperature of the acid treatment is 100° C., and the time of the acid treatment is 4 hours.
[0045] c. Mix the negative electrode material in step b with a manganese source, perform a first hydrothermal reaction, and obtain a mixed product; wherein the manganese source is potassium permanganate, the concentration of the manganese source is 5 mol / L, and the mass ratio of the negative electrode material to the manganese source is 30:1; the temperature of the first hydrothermal reaction is 100° C., and the reaction time is 60 min.
[0046] d. subjecting the mixed product to a second hydrothermal reaction with an alkaline solution, taking out the solid phase product, washing it, and then drying it to obtain an adsorbent material; wherein the alkaline solution is a sodium hydroxide solution, the concentration of the alkaline solution is 10%, the temperature of the second hydrothermal reaction is 100° C., the reaction time is 60 min, the drying temperature is 80° C., and the drying time is 24 h.
[0047] Example 3 a. Immerse the conventional commercially available waste lithium batteries in a sodium sulfate solution with a mass concentration of 5 mol / L for 4 hours for discharge, and then disassemble them to obtain the negative electrode.
[0048] b. The negative electrode in step a is subjected to acid treatment, and then solid-liquid separation is performed to obtain a negative electrode material; wherein the concentration of the acid solution in the acid treatment is 5 mol / L, the acid solution is a sulfuric acid solution, and the ratio of the volume of the acid solution to the mass of the negative electrode is 10:1; the temperature of the acid treatment is 110° C., and the time of the acid treatment is 4 h.
[0049] c. Mix the negative electrode material in step b with a manganese source, perform a first hydrothermal reaction, and obtain a mixed product; wherein the manganese source is potassium permanganate, the concentration of the manganese source is 5 mol / L, and the mass ratio of the negative electrode material to the manganese source is 30:1; the temperature of the first hydrothermal reaction is 100° C., and the reaction time is 60 min.
[0050] d. subjecting the mixed product to a second hydrothermal reaction with an alkaline solution, taking out the solid phase product, washing it, and then drying it to obtain an adsorption material; wherein the alkaline solution is a sodium hydroxide solution, the concentration of the alkaline solution is 20%, the temperature of the second hydrothermal reaction is 90° C., the reaction time is 60 min, the drying temperature is 80° C., and the drying time is 24 h.
[0051] Comparative Example 1 The method of Example 1 is adopted, except that step b is not performed.
[0052] Comparative Example 2 a. Immerse the conventional commercially available waste lithium batteries in a sodium chloride solution with a mass concentration of 2 mol / L, soak for 4 hours for discharge, and then disassemble to obtain the negative electrode.
[0053] b. The negative electrode in step a is subjected to acid treatment, and then solid-liquid separation is performed to obtain a negative electrode material; wherein the concentration of the acid solution in the acid treatment is 4 mol / L, the acid solution is a nitric acid solution, and the ratio of the volume of the acid solution to the mass of the negative electrode is 10:1; the temperature of the acid treatment is 90° C., and the time of the acid treatment is 4 h.
[0054] c. Mix the negative electrode material in step b with a manganese source, perform a first hydrothermal reaction, obtain a mixed product, filter and recover the solid phase product, wash and dry the solid phase product, and obtain an adsorption material; wherein the manganese source is potassium permanganate, the concentration of the manganese source is 4 mol / L, and the mass ratio of the negative electrode material to the manganese source is 30:1; the temperature of the first hydrothermal reaction is 100°C, and the reaction time is 40 min.
[0055] Test Case The adsorption materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested in the following manner: The warm nitrogen adsorption-desorption test (BET) was carried out on a JW-BK200C surface area and pore volume analyzer produced by Beijing Jingwei Gaobo Co., Ltd. The surface area and pore volume were calculated using the two-parameter BET equation.
[0056] A certain volume of heavy metal solution containing Cu and Al was placed in a reactor (wherein the Cu content was 245.67 mg / L; the Al content was 263.12 mg / L), and the adsorption materials provided in Examples 1 to 3 and Comparative Examples 1 to 2 were added, and the mixture was allowed to react after sufficient contact. After 120 minutes of reaction, a certain amount of the reaction solution was drawn and centrifuged. A spectrophotometer was then used to measure the absorbance of the sample after centrifugation, a standard curve was drawn, and the sample concentration was calculated based on the absorbance.
[0057] Residual rate of Cu and Al = C t / C0×100%; where C0 is the amount of Cu and Al in the initial sample, C t is the amount of Cu and Al in the sample after adsorption; Material loss rate = (m0-m t ) / m0×100%; where m0 is the initial mass of the adsorption material, m t is the mass of the adsorbed material after the reaction. The results are shown in Table 1.
[0058] Table 1
[0059] As can be seen from Table 1, the method provided in the present application is used to hydrothermally react the negative electrode material in the waste battery with the manganese source to produce more pores and active sites, and then the mixed product is subjected to a secondary hydrothermal reaction with the alkaline solution, which can further increase the pore volume of the prepared adsorption material, so that the material has a higher specific surface area, and further increase the adsorption sites of the material, so that the material has better adsorption performance. The adsorption materials provided in Examples 1 to 3 of the present application have significant advantages in adsorbing heavy metal pollutants, and the heavy metal residual rate is less than 9%, and the material loss after the reaction is small, which can reach less than 6%.
[0060] By comparing Comparative Example 1 with Example 1, it can be seen that since Comparative Example 1 was not subjected to acid treatment, the pore volume and specific surface area of the prepared adsorption material decreased. When the adsorption material provided in Comparative Example 1 was used to adsorb heavy metal pollutants, the heavy metal residual rate and material loss rate were significantly higher than those of Examples 1 to 3 of the present application.
[0061] By comparing Comparative Example 2 with Example 1, it can be seen that since Comparative Example 2 was not subjected to alkali treatment, the pore volume and specific surface area of the prepared adsorption material decreased. When the adsorption material provided in Comparative Example 1 was used to adsorb heavy metal pollutants, the heavy metal residual rate and material loss rate were significantly higher than those of Examples 1 to 3 of the present application.
[0062] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0063] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0064] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing an adsorbent material, wherein: The method includes: S0, discharging and disassembling the waste battery to obtain the negative electrode sheet; S1, subjecting the negative electrode sheet to an acid treatment, and then performing solid-liquid separation to obtain a negative electrode material; S2, mixing the negative electrode material with a manganese source, performing a first hydrothermal reaction, and obtaining a mixed product; S3, subjecting the mixed product to a second hydrothermal reaction with an alkaline solution and collecting a solid phase product.
2. The method according to claim 1, wherein: The waste battery is a battery whose negative electrode contains carbon material; The discharging comprises: immersing the waste battery in a sodium chloride or sodium sulfate aqueous solution with a concentration of more than 0.2 mol / L for more than 2 hours.
3. The method according to claim 1, wherein: The concentration of the acid solution in the acid treatment is above 2 mol / L; the acid solution comprises an oxygen-containing acid, preferably one or more of nitric acid, sulfuric acid and perchloric acid; The acid treatment temperature is above 50°C, preferably 60-90°C; the time is 2-24h, preferably 3-12h; The ratio of the volume of the acid solution to the mass of the negative electrode is 4 or more.
4. The method according to claim 1, wherein: The mass ratio of the negative electrode material to the manganese source is (20-40):1; The manganese source includes one or more of potassium permanganate, manganese dioxide and manganese nitrate; The concentration of the manganese source is 0.5-8 mol / L.
5. The method according to claim 1, wherein: In step S2, the conditions of the first hydrothermal reaction include: a temperature of 90°C or higher, preferably 90-110°C; and a time of 30 minutes or higher, preferably 40-120 minutes.
6. The method according to claim 1, wherein: In step S3, the conditions of the second hydrothermal reaction include: a temperature of 60°C or higher, preferably 90-110°C; a time of 60 min or higher, preferably 60-240 min; The alkaline solution is selected from sodium hydroxide solution and / or potassium hydroxide solution; the concentration of the alkaline solution is above 5%.
7. The method according to claim 1, wherein: The method further comprises: in step S3, after the second hydrothermal reaction, recovering the solid phase product, washing and drying it to obtain an adsorption material; The drying temperature is above 80° C. and the drying time is above 8 hours.
8. An adsorbent material prepared by the method according to any one of claims 1 to 7.
9. The adsorbent material according to claim 8, wherein The adsorbent material comprises C and manganese oxide; The specific surface area of the adsorption material is 260 m 2 / g or more, preferably 280m 2 / g or more; pore volume is 0.7cm 3 / g or more, preferably 0.9cm 3 / g or above.
10. Use of the adsorption material according to claim 8 or 9 in adsorbing heavy metal pollutants.